27 Weeks Abdominal Pregnancy wıth Mısdıagnosed at the Fırst Center, A Case Report - ERİN, Recep and TEZEL, Kadri and ISAK, Ahmed and AHMED, Samira and KUŞAK, Mustafa (International Journal of Innovative Research in Medical Science, 2019)
Abdominal pregnancy is a potentially life threatening form of ectopic gestation and is seen in 1% of all ectopic pregnancies. It’s a major cause of maternal morbidity and mortality and the potential mortality can be reduced seriously with early diagnosis and treatment. It is rarely seen in advanced pregnancy weeks due to detectability on ultrasonography in early weeks. We aimed to present a rare, misdiagnosed, abdominal pregnancy. We present a case of 20 years old primigravida with 27 weeks abdominal pregnancy who presented at the emergency room with abdominal pain and minimal vaginal bleeding. She was referred from another hospital after 2 days failed induction for incorrect diagnosis of intrauterine dead fetus. The ultrasonography was performed and seen a normal uterus with no intrauterine pregnancy but seen a single extra uterine fetus with 27 weeks gestational age lying in the peritoneal cavity on the right side. We managed successfully with laparotomy. Abdominal pregnancy is rare, and successful management depends on a high index of suspicion. Ultrasonography and serial human chorionic gonadotrophin may help in the diagnosis. Teamwork, a multidisciplinary approach and expert opinion cannot be overemphasised to ensure successful management of these cases.